Barriers to Methamphetamine Recovery in Rural Communities in North-East Thailand - Sukmak, Vatinee; Sripola, Sirirat; Intaranongpai, Siranee (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 3 (2022): July-September 2022DO - 10.14456/nujst.2022.21, 2021)
Methamphetamine addiction is a major health issue for people in Thailand, and despite efforts to help them quit permanently, large numbers of people often relapse. This descriptive phenomenological study aimed to investigate barriers to recovery from methamphetamine addiction in rural communities in north-east Thailand. Seven males who had previously participated in the outpatient recovery program at the district hospital were purposefully selected and interviewed using semi-structured guides. Their narratives were analyzed in depth in accordance with the principles of descriptive phenomenological analysis. Four themes have emerged as barriers to recovery from methamphetamine addiction: (1) a sense of no place in society, (2) feeling a lack of self-control, (3) feeling inevitably dependent on a dealer, and (4) a feeling of insufficient family support. The findings of this study provide evidence-based insight into the need to integrate community, family, and peers into any intervention in the recovery process. Mental health professionals should also listen to those facing many barriers. Developing outpatient psychosocial interventions may help to remove some barriers and improve the recovery of methamphetamine addicts. Keywords: addiction, barriers, phenomenology, methamphetamine